Ecology for a social revolution: Re-defining the role of ecological and environmental science professionals and their responsibilities towards society - Florencia Yannelli; Kristiina Visakorpi; Anni Arponen; Carlos Arnillas; Javiera Chinga Chamorro; Mariana Chiuffo; Sharon Collinge; Roger Cousens; Kadambari Devarajan; Ken Ehrlich; marilyn grell-brisk; Rebecca Kariuki; et al. (Research Ideas and Outcomes)
The sixth mass extinction and the ongoing biodiversity and climate crises demand urgent action from ecologists and environmental scientists (EESs). Despite their critical role in addressing these challenges, EESs face unclear professional responsibilities towards society, local communities and ecosystems. The 2024 ANdiNA workshop was held in Conguillío National Park in Chile, within Wallmapu the ancestral land of the Mapuche people. It gathered global EESs to explore the roles, obligations and accountability of professionals in this field. The discussions focused on the evolving responsibilities of EESs amidst the environmental crises, as well as the need for clearer frameworks to guide their actions.Key questions included the scope of EESs' professional activities, how their obligations should adapt during times of crisis and whether they should be held accountable for scientific mistakes that lead to negative societal outcomes. The workshop explored the potential for creating a codified framework, such as an oath or manifesto, to clarify EESs' professional responsibilities. Participants highlighted the importance of integrating financial, intellectual, ethical and institutional dimensions in defining these roles, particularly in how EESs engage with local communities and society.Emerging themes included the need for a shared framework to align EESs' actions, exemplified by the Conguillío Statement, which encourages collaboration, inclusivity and ethical engagement with communities, especially Indigenous ones. The workshop also emphasised the importance of solution-orientated, transformative research and advocacy, calling for a shift in how EESs approach their roles as agents of change. By critically reflecting on their responsibilities, the workshop provided a foundation for re-imagining the role of EESs in the face of global environmental crises, urging systemic, collaborative approaches to safeguarding both nature and humanity.